Reproduction in premature ovarian insufficiency patients – from latest studies to therapeutic approach - Męczekalski, Błażej; Maciejewska-Jeske, Marzena; Podfigurna, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2018)
Normal function of the ovaries, which is responsible for the hormonal and reproductive processes, is one of the most important determinants of fertility. Premature ovarian insufficiency (POI) is defined as cessation of menstrual cycle, increased serum follicle-stimulating hormone (FSH) levels, and decrease serum oestradiol levels in women before the age of 40 years. POI concerns about 1% of women and is characterised by severely diminished fertility. For the POI patient, this is one of the most dramatic problems. It influences their psychological status and functioning in society. The chance for spontaneous conception is very limited and ranges from 4 to 8%. For contemporary medicine, infertility treatment in POI patients is a challenge. The problem is that there are no effective therapies to augment ovarian activity in POI patients. At present, oocyte donation is regarded as the only proven method in the treatment of infertility in POI patients. However, nowadays we can observe important progress in the development of fertility preservation methods. In the POI field it refers to cryopreservation of oocytes, embryos, and ovarian tissue. Additionally, new methods known as in vitro activation of dormant follicles and possible use of stem cells should be mentioned.